2009
DOI: 10.1039/b905665c
|View full text |Cite
|
Sign up to set email alerts
|

Size-dependent cation transport by cyclic α-peptoid ion carriers

Abstract: N-Benzyloxyethyl macrocyclic peptoids 3 and 4 were synthesized and subjected to alkali metal binding studies; these compounds, plus the known 1 and 2, when subjected to ion transport studies, demonstrated size-dependent selectivity for the first group alkali metals cation transport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 23 publications
1
44
0
Order By: Relevance
“…cyclo-(Nspe-Nspe-Nph) 2 (9) 2 7 cctcct cyclo-(Nme) 6 (10) 1 5 cctcct cyclo-(Npm 2 -Nph-Npm 2 -Nnp) (11) 2 8 all-trans cyclo-(Nme) 6 Na complex (10˙Na + ) 1 5 all-trans cyclo-(Nbe) 6 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…cyclo-(Nspe-Nspe-Nph) 2 (9) 2 7 cctcct cyclo-(Nme) 6 (10) 1 5 cctcct cyclo-(Npm 2 -Nph-Npm 2 -Nnp) (11) 2 8 all-trans cyclo-(Nme) 6 Na complex (10˙Na + ) 1 5 all-trans cyclo-(Nbe) 6 …”
Section: Resultsmentioning
confidence: 99%
“…32 and 33). Coloured side-chains highlight the macrocycle pre-organization; c) crystal packing of cyclo-(NMe) 6 and d) of the corresponding Na + complex as viewed along the a axis. Side by side intertubular contacts are provided by cis carbonyl groups, which Fig.…”
Section: Heptameric Cyclic Peptoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in a follow-up study, these groups reported cation transport carried by cyclic peptoids across a phospholipid membrane. [52] Two additional cyclic peptoids, an octamer and a decamer, were synthesized and characterized, and their size-dependent selectivity for first group alkali metal cation transport was demonstrated.…”
Section: Metal Coordination In Peptidomimetic Foldamersmentioning
confidence: 99%
“…This conjugate was shown to bind the same monoclonal antibodies as HNE itself and therefore may be of use as a new measles vaccine. The development of a novel approach to macrocyclic peptoids for use as ionophores has been reported (De Cola et al, 2009). Cyclotides, disulfide rich cyclic peptides, have been isolated for the first time from the Melicytus family of plants (Trabi et al, 2009).…”
Section: The Chemical Biology Of Proteinsmentioning
confidence: 99%